Hyponatremia in horses with septic pneumopathy - Alessandro Migliorisi; Anne Barger; Scott Austin; Jonathan H. Foreman; Pamela Wilkins (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Hyponatremia is common in horses with bacterial pleuropneumonia, but no further characterization of this abnormality has been reported. Objectives Describe admission plasma sodium concentration ([Na]) in horses with septic pneumopathy and evaluate any association of plasma [Na] with markers of systemic inflammation. Animals Medical records of horses >1 month of age that between 2008 and 2021 had a transtracheal aspirate (TTA) performed, abnormal TTA cytology, positive TTA culture, pulmonary disease on ultrasonography, radiography or both, and plasma [Na] assessed by direct ion‐selective‐electrode (dISE). Horses with concurrent diarrhea or azotemia were excluded. Methods Clinical and clinicopathological variables of interest between hypo‐ and normonatremic horses were compared. Spearman correlation and Fisher exact tests were used to identify significant associations (P < .05). Results Twenty of 35 horses had hyponatremia (median, 132 mmol/L; 25‐75th interquartile range [IQR], 129.7‐133.1 mmol/L; reference range, 134.2‐138.4 mmol/L). A higher proportion of horses with systemic inflammatory response syndrome (SIRS) had hyponatremia (P = .01). Hyponatremic patients had higher mean plasma fibrinogen concentration (461 ± 160.5 mg/dL; P = .01) and higher rectal temperature (38.8 ± 0.7°C; P = .02) than normonatremic horses. Negative correlations were found between plasma [Na] and fibrinogen (P = .001; ρ = −0.57) concentrations and between plasma [Na] and rectal temperature (P = .001; ρ = −0.51). Presence or absence of pleural effusion did not influence severity of hyponatremia. Mean duration of hospitalization was longer (P = .04) in hyponatremic horses (9.8 ± 6.6 days). Conclusions and Clinical Importance Hyponatremia at admission is associated with the presence of inflammation, SIRS, and with longer duration of hospitalization.